Effects of restrictive harvest criteria on antler size of hunter‐harvested male white‐tailed deer and hunter opportunity - William D. Gulsby; Charlie H. Killmaster; John W. Bowers; Karl V. Miller (Wildlife Society Bulletin)
ABSTRACT Antler‐based selective harvest criteria (SHC; e.g., number of points) are a commonly used and effective method of limiting harvest of 1.5‐year‐old male white‐tailed deer (Odocoileus virginianus). However, previous research has shown SHC that allow disproportionate harvest of young males with large antlers may reduce average antler size within older (≥2.5‐yr) age classes. We used hunter‐harvest data collected from 10 wildlife management areas in Georgia, USA, during 2003–2013 to compare cohort antler size and other factors among areas with varying or no SHC. Three of the areas restricted harvest to males with one antler beam ≥41 cm long or an antler spread ≥38 cm (BS), and another 3 restricted harvest to males with ≥4 antler points on one side (4OS). Any male with visible antlers was eligible for harvest on the remaining areas. There was no evidence that either BS or 4OS criteria led to a decrease in antler size of harvested males ≥2.5 years old. Both SHC protected ≥96% of 1.5‐year males from harvest. There was also evidence to suggest the BS criteria increased mean antler size of harvested males and annual harvest rates of 3.5‐year males. However, the 4OS criteria protected 49%, 16%, and 9% of 2.5, 3.5, and ≥4.5‐year males, respectively. The BS criteria protected 77%, 33%, and 10% of the same age classes. These findings suggest restrictive SHC can prevent decline in antler size of harvested males and increase opportunity for hunters to harvest older males with larger antlers, with the added biological benefit of increasing the population age structure. However, restrictive SHC may unintentionally protect a significant proportion of ≥2.5‐year males from harvest. As previously suggested, managers interested in SHC should carefully research site‐ and age‐specific antler size to avoid implementation of criteria that are either too restrictive or permissive. © 2019 The Wildlife Society